PROBLEMATIKA LEARNING LOSS DI SDN TAKEN AKEN KECAMATAN JANAPRIA - Nurhariansyah Astari; Ratu Wahyuni, Dewi; Mujaranah; Halimatus Sa'diyah; Redan Werang, Basilius (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Learning loss is one of the consequences of disrupted learning processes that affects students' competency achievement, particularly at the elementary school level. This study aims to describe the learning loss problems experienced at SDN Taken Aken, identify the contributing factors, and explain the school's efforts to address them. This research employed a qualitative approach using a descriptive method. Data were collected through observations, interviews with the principal, teachers, and students, as well as documentation, and were analyzed through data reduction, data display, and conclusion drawing. The findings indicate that learning loss is characterized by declining literacy and numeracy skills, low learning motivation, disparities in students' abilities, and limited parental support for learning at home. These conditions were influenced by the limited effectiveness of learning during the pandemic, unequal access to learning resources, and varying levels of parental support. To overcome these challenges, the school implemented diagnostic assessments, remedial programs, literacy and numeracy reinforcement, student-centered active learning, and strengthened collaboration with parents. The study concludes that addressing learning loss requires sustainable learning strategies and strong collaboration among schools, families, and students to optimize learning recovery.